ASSESSMENT OF THE DYNAMICS OF VEGETATION COVER IN THE MOIYNKUM SAND MASSIF UNDER CLIMATE CHANGE CONDITIONS (Journal of Geography and Environmental Management, 2025)
Effective use of pasture lands in sandy massifs and monitoring of their condition in the context of global climate change is a very urgent issue for our country, which occupies 70% of the territory of semi-desert and desert zones. In this research paper, we analyzed the dynamics of vegetation cover changes in the Moyinkum sand massif using remote sensing data (MOD13Q1) and comprehensive field studies, as well as long-term climate data.  In terms of vegetation indices (NDVI, EVI) by 2000-2024. Significant improvement of vegetation cover is observed in some parts of the Moyinkum sandy massif.In order to verify the results obtained based on remote sensing data, field work was organized in the study area (22 points) and long-term climatic data from 5 meteorological stations (zhelob, Ulanbel, Kulan, Kamen and Moyinkum) were analyzed. The average annual temperature in 2000-2023 is higher than in 1980-2000, MS – 1.1℃, MS – 1.0℃, MS – 1.1℃ and MS – 1.0℃.  In addition, the average annual precipitation in 2000-2023 increased by furrowed MS-12.1 mm, Ulanbel MS – 10.4 mm, Kulan MS – 20.5 mm, stony 9.9 mm and Moyinkum MS – 5.5 mm compared to 1980-2000. Analyzing the climatic data based on data from meteorological stations in the study area, it can be assumed that the improvement of vegetation in recent years in the territory has been influenced by climatic conditions, including an increase in precipitation.
Keywords: Moyinkum sand massif; climate change; remote sensing of the Earth; NDVI; EVI; field works